The Transcription Factor MafB Regulates the Susceptibility of Bactrocera dorsalis to Abamectin via GSTz2 - Tang, Guang-Hui; Xiong, Ying; Liu, Yi; Song, Zhong-Hao; Yang, Yang; Shen, Guang-Mao; Wang, Jin-Jun; Jiang, Hong-Bo (Frontiers in Physiology, 2019)
Pesticide resistance is a serious problem that poses a major challenge to pest control. One of the most potent resistance mechanisms is the overexpression of genes coding for detoxification enzymes. The expression of detoxification genes is regulated by a series of transcription factors. Previous studies have revealed that the increase expression of detoxification genes contributes to the insecticide tolerance of Bactrocera dorsalis. Our objective was thus to identify the transcription factors involved in this process. Temporal expression profiles showed that the transcription factor MafB and detoxification genes were expressed highly in the fat body. Further analysis showed that the expression of MafB, GSTz2, and CYP473A3 were induced by abamectin. Disruption of the MafB transcription factor through RNA interference decreased the transcript levels of GSTz2 and CYP473A3 and increased the susceptibility to abamectin significantly. Direct silencing of the expression of GSTz2 also increased susceptibility to abamectin, while CYP473A3 did not. In conclusion, these results suggest that the expression of GSTz2 and CYP473A3 was regulated by the transcription factor MafB, and the up-regulation of GSTz2 via MafB decreased the susceptibility of B. dorsalis to abamectin.